علامہ اقبالؔ کے چند فارسی اشعار کی غیر مطبوعہ شرح: Unpublished interpretation of some Persian verses of Allama Iqbal - ڈاکٹر ارشد محمود ناشاد (Tashkeel e Jadeed, 2023)
Understanding the thought-provoking and philosophical poetry of Iqbal is not easy for any level of reader, because the formation of Iqbal's ideas includes many kinds of intellectual schools and sources. The main source of Iqbal's thought is the Holy Qur'an. A vast world of meaning is hidden in his similes, metaphors, allusions, and compounds, which cannot be understood without deep study and extensive knowledge. This is the reason that the interpretation of Iqbal's poetry started during his life. Among the early interpreters of Iqbal's poetry were those who had the opportunity to meet Iqbal and sit in his gatherings, and all of them were fully aware and familiar with the meaning of Iqbal's message of poetry. Among these commentators of Iqbal, the names of Maulana Ghulam Rasool Mehr, Yusuf Saleem Chishti and Sufi Ghulam Mustafa Tabassum are especially worth mentioning. Sufi Ghulam Mustafa Tabassum was an eminent poet, writer and scholar of Persian, Urdu and Punjabi. Apart from articles and books, he presented hundreds of programs on Radio Pakistan to make the new generations aware of Iqbal's message. Although his interpretations have been published in the form of various books, some of his interpretations remain unpublished. Through this article, unpublished interpretations of five Persian poems of Iqbal are being presented for the first time.